KEPATUHAN PASIEN RAWAT JALAN POLI PARU DALAM PENGGUNAAN OBAT ANTI TUBERKULOSIS (OAT) DI RUMAH SAKIT KARTIKA HUSADA JATIASIH BEKASI - Marta Halim; Alifa Sabrina Sabrina; Muhamad Aris (Jurnal Farmasi IKIFA, 2023)
Tuberculosis is a direct infectious disease caused by Mycobacterium tuberculosis. Globally, it is estimated that 10 million people suffer from TB in 2019. Despite the decline in new TB cases, in 2015 – 2019 there was only a 9% decrease in TB cases, but not fast enough to reach the target of reducing cases of 20%. Adherence to taking medication is a key factor in the success of treatment. This study aims to determine the level of outpatient compliance of pulmonary polyclinic in the use of anti-tuberculosis drugs (OAT) at Kartika Husada Hospital, Jatiasih. The method used is descriptive method. Sampling in this study was based on inclusion and exclusion criteria. The sampling technique in this study used purposive sampling. The results showed that high adherence was 10 patients (24.39%), moderate adherence was 28 patients (68.29%) and low adherence was 3 patients (7.32%). It was councluded that the level of adherence to medication in tuberkulosis patients at Kartika Husada Hospital Jatiasih had moderate adherence (68,29%).